Effects of Pregnancy Planning, Complication, and Social Support on Depression in Pregnant Women - Rosid, Sultonnur; Umar, Alwan Dhafi; Putra, Gilang Pamungkas Ardi; Murti, Bhisma; Handayani, Anggun Fitri (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2024)
Background: Depression is a mental symptom that arises with symptoms of loss of spirit, mood swings, and disruption of daily activities. Symptoms of depression are commonly experienced by pregnant women, but symptoms of depression can be treated and prevented. Recognizing the causes or determinants of depression in pregnant women is important to prevent the onset of depressive symptoms. This study aimed to estimate the effect of planning, complications, and social support on depression in pregnant women. Subjects and Method: A systematic review and meta-analysis was conducted using PRISMA guidelines and the PICO model. The articles used are between 2017 and 2023. Population = pregnant women. Intervention = Poor planning, complications, low social support. Comparison= Good planning, no complications, high social support. Outcome = Depression. Articles are compiled from databases such as Google Scholar, PubMed, and Science Direct. Literature search using the keywords